2017
DOI: 10.1097/igc.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcome of High-Grade, Early 1-Stage Endometrioid Endometrial Carcinoma With Adjuvant Chemotherapy and Radiotherapy

Abstract: Adjuvant chemotherapy and radiotherapy in early-stage high-grade endometrioid endometrial carcinoma results in improved disease-specific and overall survival compared to radiotherapy alone. Yet, due to the relatively low numbers, validation of these findings is needed in large prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Outside of prospective trials, there have been several studies examining recurrence in solely early-stage patients with EC ( 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). However, some of these studies include a heterogenous group of women with non-endometrioid histologies, such as serous carcinoma, which are known to have a poor prognosis ( 8 , 10 , 11 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of prospective trials, there have been several studies examining recurrence in solely early-stage patients with EC ( 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). However, some of these studies include a heterogenous group of women with non-endometrioid histologies, such as serous carcinoma, which are known to have a poor prognosis ( 8 , 10 , 11 , 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some of these studies include a heterogenous group of women with non-endometrioid histologies, such as serous carcinoma, which are known to have a poor prognosis ( 8 , 10 , 11 , 21 , 22 ). All of these studies also include women who received various adjuvant treatments ( 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). Adjuvant therapy is known to significantly impact recurrence rates ( 3 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 3 ] Patients receiving radiation have a significantly reduced recurrence and metastasis rate, and disease-free survival is greater. [ 4 , 5 ] However, side effects of radiation have been widely reported, including impaired fertility, [ 6 ] secondary malignancy, [ 7 , 8 ] and lung metastasis. [ 9 ] Thus, accurate diagnosis of lymph invasion is critical to guide adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been conducted to evaluate the efficacy of chemotherapy for HR stage I to II EC patients. Reynaers et al [ 25 ] retrospectively analyzed 116 patients with stage IB-II grade 3 disease and concluded that adjuvant chemotherapy and RT resulted in improved OS compared to RT alone. Smogeli et al [ 26 ] demonstrated that HR EC patients had acceptable vaginal/pelvic control rates after adjuvant chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%